Automobile seat cover with good air permeability and preparation method thereof
By adopting a multi-layer structural design in the car seat cover, including L-PET and PET short fiber layers and antibacterial latex layers, and setting anti-slip surfaces and breathable holes on the surface, the breathability and wear resistance of existing car seat fabrics are solved. The problem of insufficient degree improves breathability and safety.
Patent Information
- Application Number
- CN202411564214.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
The existing car seat fabric has poor breathability and wear resistance, which leads to the driver's butt sweating and prone to illness after sitting for a long time.
Using a structural design including a first fiber layer, a latex layer and a second fiber layer, the first fiber layer and the second fiber layer are composed of L-PET and PET short fiber layers, and the back of the latex layer is fixed with a protective layer, and the Anti-slip surfaces and breathable holes are provided on the surface of the protective layer.
Through the cooperation of the resilience of the latex layer and the breathable holes, the breathability of the car seat cover is significantly improved. At the same time, the porous structure of the latex layer and the use of antibacterial materials improves safety and structural toughness.
Smart Images

Figure CN119388850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile seat covers, and more particularly to an automobile seat cover with good air permeability and a preparation method thereof. Background Art
[0002] Car seat fabrics need to have the characteristics of comfort, safety and decorativeness, and the fabrics have high performance requirements. However, the textile fabrics in existing car seat fabrics generally use ordinary textile fabrics, which have poor air permeability and wear resistance. Drivers sit for a long time, their buttocks are prone to sweating and getting sick. Therefore, in order to solve the above problems, a car seat cover with good air permeability and a preparation method thereof are very necessary. Summary of the invention
[0003] The main technical problem solved by the present invention is to provide a car seat cover with good air permeability and a preparation method thereof, which can solve the problems raised by the above background technology.
[0004] To solve the above technical problems, according to one aspect of the present invention, more specifically, a car seat cover with good air permeability includes a first fiber layer, a latex layer is fixedly bonded to the back of the first fiber layer, a second fiber layer is fixedly bonded to the back of the latex layer, the first fiber layer and the second fiber layer are short fiber layers mixed with L-PET and PET, a first protective layer is fixedly bonded to the back of the second fiber layer, a second protective layer is fixedly bonded to the back of the first protective layer, an anti-slip surface is fixedly provided on the surface of the second protective layer, a plurality of air permeable holes are penetrated between the anti-slip surface and the second protective layer and the second fiber layer, the first protective layer is a flame retardant layer, and the second protective layer is a waterproof, oil-proof and antistatic composite layer.
[0005] Furthermore, the first protective layer is a polypropylene resin layer, the thickness of the first protective layer is 0.15 mm, and it mainly includes the following weight components: polypropylene resin: 100 parts; magnesium aluminum hydrotalcite colloid: 10-15 parts; retention aid CPAM: 0.05-0.1 parts; sepiolite: 2-3 parts; coupling agent vinyl trimethoxy silane: 0.5-1.5 parts; white oil: 3-4.0 parts; stearic acid: 0.4-1.0 parts; red phosphorus: 0.5-1.0 parts.
[0006] Furthermore, the preparation method of the magnesium-aluminum hydrotalcite colloid is as follows: Mg(NO3)2.6H2O and Al(NO3)3.9H2O with a magnesium-aluminum ratio of 3:1 are dissolved in deionized water at room temperature, and the total ion concentration is fixed at 0.5 mol / L, and then the obtained solution is slowly added to a sodium carbonate solution with a mass concentration of 10% under stirring, and after the addition, it is vigorously stirred for 1.5 hours and slowly stirred for 2 hours. During this process, a precipitate will be generated, and it is allowed to stand at room temperature for 48 hours, and filtered under reduced pressure. After the filter cake is washed twice with deionized water, it is peptized at 60-80°C for 6 hours to obtain the hydrotalcite colloid.
[0007] Furthermore, the second protective layer is a PE / PA composite film, the thickness of the second protective layer is 0.2-0.3mm, and the second protective layer includes the following weight components: PE: 50-60 parts; PA: 45-55 parts; glycerol monostearate: 7-9 parts; sorbitan polyoxyethylene ether: 1-3 parts; vinyl trimethoxy silane: 0.7-0.9 parts; a mixture of paraffin oil and paraffin in a weight ratio of 1:2: 1.5-2 parts; chitosan: 1-2 parts; dioctyl phthalate: 1-2 parts; a mixture of calcium zinc composite stabilizer and pentaerythritol in a weight ratio of 1:3: 0.7-0.9 parts; maleic anhydride grafted polyethylene PE-g-MAH: 0.7-0.9 parts; calcium carbonate: 0.5-1.5 parts; methacrylate-butadiene-styrene copolymer: 0.1-0.5 parts.
[0008] According to another aspect of the present invention, there is provided a method for preparing a car seat cover with good air permeability, comprising the following steps: S1. Preparation of PET staple needle-punched nonwoven fabric layer: two types of PET fibers with different mass percentages are respectively opened into mixed fibers and placed in a mixing box for mixing, then the mixed uniform fibers are combed flat and placed in a web laying machine to form a multi-layer fiber web, and then needle-punched and rolled into a PET staple needle-punched nonwoven fabric layer by a roll-forming machine; S2, preparation of antibacterial latex layer: natural latex and water are mixed in equal proportions, added to supramolecular solution, filtered and freeze-dried to obtain natural latex, and natural latex is added to chitosan and dissolved in acetic acid-water mixture, and nanocellulose, inorganic filler material, glutaraldehyde and silane modifier are added at the same time, reacted, filtered, freeze-dried and crushed to obtain natural latex masterbatch, natural latex masterbatch, natural antibacterial agent, oxidant, nano-silica and pore-piercing agent are stirred and mixed, and then injected into a mold, and after curing and molding, cooled, washed, dried and cut to obtain antibacterial latex layer; S3, laminating layer preparation: sandwiching the antibacterial latex layer between two PET staple needle-punched non-woven fabric layers and laminating them through a barb machine, then heating to melt the L-PET inside the two PET staple needle-punched non-woven fabric layers to bond and fix various fibers to the latex layer, and finally rolling them; S4, preparation of flame retardant layer: prepare ingredients according to the flame retardant layer formula, add the prepared ingredients into a mixer for mixing, mix evenly, put into the mixer for low speed mixing, and finally put into the extruder for plasticization, pelletizing, die cutting and winding; S5. Preparation of waterproof, oil-proof and antistatic composite layer: the ingredients are prepared according to the formula of the waterproof, oil-proof and antistatic composite layer, the prepared materials are added to a mixer and mixed evenly, after being mixed evenly, transferred to a cooling mixer for low-speed mixing, and finally put into an extruder for plasticization, pelletizing, and finally die-cutting and winding; S6, composite processing: firstly, the prepared flame retardant layer is effectively composited with the back of the laminating layer through a hot stamping laminating machine, and then the prepared waterproof, oil-proof and antistatic composite layer is effectively composited with the flame retardant layer on the back of the laminating layer through a hot stamping laminating machine; S7, cutting and molding: the product is shaped, heated, and molded, anti-slip patterns are pressed on the surface, and air holes are punctured, and finally the product is cut and assembled into a car seat cover.
[0009] Furthermore, the preparation method of the supramolecular solvent in S2 is: dissolving a surfactant in tetrahydrofuran to obtain a surfactant solvent, adding water to the solution and vortexing it, performing centrifugal separation after ultrasonication, and taking the lower layer as the supramolecular solvent.
[0010] Furthermore, the inorganic filling material in S2 is one or more of nano-silicon dioxide, nano-calcium carbonate, and nano-aluminum carbonate; the silane modifier is one of tetraalkyltriethoxysilane, tetraalkyltrimethoxysilane, hexaalkyltriethoxysilane, and octaalkyltrimethoxysilane; the acetic acid-water mixture, natural latex, nanocellulose, inorganic filling material, glutaraldehyde, and silane modifier are 50-65 parts, 30-40 parts, 5-15 parts, 4-6 parts, 4-6 parts, and 3-5 parts by mass, respectively.
[0011] Furthermore, the natural antibacterial agent in S2 is: coptis chinensis alcohol extract, garlic alcohol extract, and aloe alcohol extract are mixed in a mass ratio of 1:2-3:1, the oxidant is one or more of aloe water extract, grape seed alcohol extract, and tea alcohol extract, the pore-forming agent is one or more of water, ethanol, and ethyl acetate, and the natural latex masterbatch, natural antibacterial agent, oxidant, nano-silica, and pore-forming agent are 75-85 parts, 4-6 parts, 1-4 parts, 5-15 parts, and 5-10 parts by mass, respectively.
[0012] The beneficial effects of the car seat cover with good air permeability of the present invention are: By providing a first fiber layer, a latex layer and a second fiber layer, the overall air permeability is improved through the resilience of the latex layer and the breathable holes during use. At the same time, a pore-piercing agent is used in the preparation of the latex layer to make the prepared latex pad have a porous structure, which further improves the air permeability. At the same time, a variety of antibacterial materials are arranged inside, which makes it safer to use, and forms a strict fiber structure with the first fiber layer and the latex layer, thereby improving the toughness of the structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0014] Figure 1 A schematic diagram of the internal structure of a car seat cover with good air permeability and a preparation method thereof according to the present invention; Figure 2 The present invention is a schematic diagram of the process flow of a car seat cover with good air permeability and a preparation method thereof.
[0015] In the figure: 1. first fiber layer; 2. latex layer; 3. second fiber layer; 4. first protective layer; 5. second protective layer; 6. anti-slip surface; 7. breathable holes. DETAILED DESCRIPTION
[0016] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.
[0017] like Figure 1-Figure 2 As shown, according to one aspect of the present invention, there is provided a car seat cover with good air permeability, comprising a first fiber layer 1, a latex layer 2 is fixedly bonded to the back of the first fiber layer 1, a second fiber layer 3 is fixedly bonded to the back of the latex layer 2, the first fiber layer 1 and the second fiber layer 3 are short fiber layers formed by a mixture of L-PET and PET, a first protective layer 4 is fixedly bonded to the back of the second fiber layer 3, a second protective layer 5 is fixedly bonded to the back of the first protective layer 4, an anti-slip surface 6 is fixedly provided on the surface of the second protective layer 5, a plurality of air permeable holes 7 are penetrated between the anti-slip surface 6 and the second protective layer 5 and the second fiber layer 3, the first protective layer 4 is a flame retardant layer, and the second protective layer 5 is a waterproof, oil-proof and antistatic composite layer.
[0018] In this embodiment, the first protective layer 4 is a polypropylene resin layer, the thickness of the first protective layer 4 is 0.15 mm, and it mainly includes the following weight components: polypropylene resin: 100 parts; magnesium aluminum hydrotalcite colloid: 10-15 parts; retention agent CPAM: 0.05-0.1 parts; sepiolite: 2-3 parts; coupling agent vinyl trimethoxy silane: 0.5-1.5 parts; white oil: 3-4.0 parts; stearic acid: 0.4-1.0 parts; red phosphorus: 0.5-1.0 parts.
[0019] In this embodiment, the preparation method of magnesium aluminum hydrotalcite colloid is as follows: Mg(NO3)2.6H2O and Al(NO3)3.9H2O with a magnesium aluminum ratio of 3:1 are dissolved in deionized water at room temperature, and the total ion concentration is fixed at 0.5 mol / L, and then the obtained solution is slowly added to a sodium carbonate solution with a mass concentration of 10% under stirring, and after the addition, it is vigorously stirred for 1.5 hours and slowly stirred for 2 hours. During this process, a precipitate is generated, and it is allowed to stand at room temperature for 48 hours, and is filtered under reduced pressure. After the filter cake is washed twice with deionized water, it is peptized at 60-80°C for 6 hours to obtain hydrotalcite colloid.
[0020] In the present embodiment, the second protective layer 5 is a PE / PA composite film, the thickness of the second protective layer 5 is 0.2-0.3 mm, and the second protective layer 5 includes the following weight components: PE: 50-60 parts; PA: 45-55 parts; glycerol monostearate: 7-9 parts; sorbitan polyoxyethylene ether: 1-3 parts; vinyl trimethoxy silane: 0.7-0.9 parts; a mixture of paraffin oil and paraffin in a weight component ratio of 1:2: 1.5-2 parts; chitosan: 1-2 parts; dioctyl phthalate: 1-2 parts; a mixture of calcium zinc composite stabilizer and pentaerythritol in a weight component ratio of 1:3: 0.7-0.9 parts; maleic anhydride grafted polyethylene PE-g-MAH: 0.7-0.9 parts; calcium carbonate: 0.5-1.5 parts; methacrylate-butadiene-styrene copolymer: 0.1-0.5 parts.
[0021] The present invention also provides a method for preparing a car seat cover with good air permeability, comprising the following steps: S1. Preparation of PET staple needle-punched nonwoven fabric layer: 20-25% and 70-75% PET fibers are respectively opened into mixed fibers and put into a mixing box for mixing, then the mixed uniform fibers are combed flat and put into a web laying machine to form a multi-layer fiber web, and then needle-punched and rolled into a PET staple needle-punched nonwoven fabric layer by a roll-forming machine; S2. Preparation of antibacterial latex layer: natural latex and water are mixed in equal proportions, added to a supramolecular solution of 3-4% of the total volume, ultrasonicated for 5-7 minutes, filtered and freeze-dried to obtain natural latex, and natural latex is added to chitosan, dissolved in an acetic acid-water mixture, and nanocellulose, inorganic filler, glutaraldehyde, and silane modifier are added at the same time, reacted at 500-900rpm and 45-55℃ for 1-3h, filtered, freeze-dried, and crushed to obtain natural latex masterbatch, natural latex masterbatch, natural antibacterial agent, oxidant, nanosilica, and pore-forming agent are stirred and mixed, heated and melted at 100-150℃, and then injected into a mold, and after solidification and molding, kept at 55-75℃ for 3-5h, cooled, washed, dried and cut to obtain an antibacterial latex layer, and the preparation method of supramolecular solvent is as follows: a surfactant is dissolved in tetrahydrofuran to obtain a 3-5 g / mL surfactant solvent, 10-15 times the volume of water is added to the solution, vortexed, and ultrasonicated for 10-15 min later, centrifugation is performed to separate phases, and the lower layer is taken out to be the supramolecular solvent. The concentration of acetic acid in the acetic acid-water mixture is 1-2% (v / v); the inorganic filler material is one or more of nano-silicon dioxide, nano-calcium carbonate, and nano-aluminum carbonate; the silane modifier is one of tetraalkyltriethoxysilane, tetraalkyltrimethoxysilane, hexaalkyltriethoxysilane, and octaalkyltrimethoxysilane; the acetic acid-water mixture, natural latex, nanocellulose, inorganic filler material, glutaraldehyde, and silane modifier are 50-65 parts, 30-4 parts by mass, respectively. 0 parts, 5-15 parts, 4-6 parts, 4-6 parts, 3-5 parts, the natural antibacterial agent is: coptis chinensis alcohol extract, garlic alcohol extract, aloe alcohol extract are mixed in a mass ratio of 1:2-3:1, the oxidant is one or more of aloe water extract, grape seed alcohol extract, and tea alcohol extract, the pore-forming agent is one or more of water, ethanol, and ethyl acetate, and the natural latex masterbatch, natural antibacterial agent, oxidant, nano-silica, and pore-forming agent are 75-85 parts, 4-6 parts, 1-4 parts, 5-15 parts, and 5-10 parts by mass respectively; S3, laminating layer preparation: sandwiching the antibacterial latex layer between two PET staple needle-punched non-woven fabric layers and laminating them through a barb machine, then heating to melt the L-PET inside the two PET staple needle-punched non-woven fabric layers to bond and fix various fibers to the latex layer, and finally rolling them; S4, preparation of flame retardant layer: prepare ingredients according to the flame retardant layer formula, add the prepared ingredients into a mixer for mixing, the mixing temperature is 110-130°C, the mixing time is 8-11 minutes, after mixing evenly, put into the mixer at 40-55°C and stir at a low speed for 5-11 minutes, finally put into the extruder at 160-180°C for plasticization, pelletizing, and finally die-cutting and winding; S5. Preparation of waterproof, oil-proof and antistatic composite layer: the ingredients are prepared according to the formula of the waterproof, oil-proof and antistatic composite layer, and the prepared materials are added into a mixer and mixed evenly. The mixing temperature is 100-120°C, and the mixing time is 8-11 minutes. After mixing evenly, the mixture is transferred to a cooling mixer and stirred at a low speed at 30-40°C for 5-11 minutes, and finally enters an extruder for plasticization and pelletizing at 170-185°C, and finally die-cutting and winding; S6, composite processing: firstly, the prepared flame retardant layer is effectively composited with the back of the laminating layer through a hot stamping laminating machine, wherein the composite temperature is 160-170°C, and then the prepared waterproof, oil-proof and antistatic composite layer is effectively composited with the flame retardant layer on the back of the laminating layer through a hot stamping laminating machine, wherein the composite temperature is 160-170°C; S7, cutting and molding: the product is shaped, heated, and molded, anti-slip patterns are pressed on the surface, and air holes are punctured, and finally the product is cut and assembled into a car seat cover.
[0022] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. A car seat cover with good air permeability, comprising a first fiber layer (1), characterized in that: The first fiber layer (1) is fixedly bonded with a latex layer (2) on the back, and the latex layer (2) is fixedly bonded with a second fiber layer (3) on the back. The first fiber layer (1) and the second fiber layer (3) are short fiber layers formed by a mixture of L-PET and PET. The second fiber layer (3) is fixedly bonded with a first protective layer (4) on the back, and the first protective layer (4) is fixedly bonded with a second protective layer (5) on the back. The second protective layer (5) is fixedly provided with an anti-slip surface (6) on its surface, and a plurality of air-permeable holes (7) are provided through the anti-slip surface (6), the second protective layer (5) and the second fiber layer (3). The first protective layer (4) is a flame-retardant layer, and the second protective layer (5) is a waterproof, oil-proof and antistatic composite layer.
2. The car seat cover with good air permeability according to claim 1, characterized in that: The first protective layer (4) is a polypropylene resin layer. The thickness of the first protective layer (4) is 0.15 mm, and the first protective layer (4) mainly comprises the following components by weight: polypropylene resin: 100 parts; magnesium aluminum hydrotalcite colloid: 10-15 parts; retention agent CPAM: 0.05-0.1 parts; sepiolite: 2-3 parts; coupling agent vinyl trimethoxy silane: 0.5-1.5 parts; white oil: 3-4.0 parts; stearic acid: 0.4-1.0 parts; red phosphorus: 0.5-1.0 parts.
3. The car seat cover with good air permeability according to claim 2, characterized in that: The preparation method of the magnesium-aluminum hydrotalcite colloid is as follows: Mg(NO3)2.6H2O and Al(NO3)3.9H2O with a magnesium-aluminum ratio of 3:1 are dissolved in deionized water at room temperature, and the total ion concentration is fixed at 0.5 mol / L, and then the obtained solution is slowly added to a sodium carbonate solution with a mass concentration of 10% under stirring, and after the addition, it is vigorously stirred for 1.5 hours and slowly stirred for 2 hours. During this process, a precipitate is generated, and it is allowed to stand at room temperature for 48 hours, and is filtered under reduced pressure. After the filter cake is washed twice with deionized water, it is peptized at 60-80°C for 6 hours to obtain the hydrotalcite colloid.
4. The car seat cover with good air permeability according to claim 1, characterized in that: The second protective layer (5) is a PE / PA composite film, the thickness of the second protective layer (5) is 0.2-0.3 mm, and the second protective layer (5) comprises the following components by weight: PE: 50-60 parts; PA: 45-55 parts; glycerol monostearate: 7-9 parts; sorbitan polyoxyethylene ether: 1-3 parts; vinyl trimethoxy silane: 0.7-0.9 parts; a mixture of paraffin oil and paraffin in a weight ratio of 1:2: 1.5-2 parts; chitosan: 1-2 parts; dioctyl phthalate: 1-2 parts; a mixture of calcium zinc composite stabilizer and pentaerythritol in a weight ratio of 1:3: 0.7-0.9 parts; maleic anhydride grafted polyethylene PE-g-MAH: 0.7-0.9 parts; calcium carbonate: 0.5-1.5 parts; methacrylate-butadiene-styrene copolymer: 0.1-0.5 parts.
5. A method for preparing a car seat cover with good air permeability, characterized in that: The following steps are involved: S1. Preparation of PET staple needle-punched nonwoven fabric layer: opening two PET fibers with different mass percentages into mixed fibers and putting them into a mixing box for mixing, then combing the mixed uniform fibers and putting them into a web laying machine to lay a multi-layer fiber web, and then performing a needle punching process and then winding them into a PET staple needle-punched nonwoven fabric layer by a rolling machine; S2, preparation of antibacterial latex layer: natural latex and water are mixed in equal proportions, added to supramolecular solution, filtered and freeze-dried to obtain natural latex, and natural latex is added to chitosan and dissolved in acetic acid-water mixture, and nanocellulose, inorganic filler material, glutaraldehyde and silane modifier are added at the same time, reacted, filtered, freeze-dried and crushed to obtain natural latex masterbatch, natural latex masterbatch, natural antibacterial agent, oxidant, nano-silica and pore-piercing agent are stirred and mixed, and then injected into a mold, and after curing and molding, cooled, washed, dried and cut to obtain antibacterial latex layer; S3, laminating layer preparation: sandwiching the antibacterial latex layer between two PET staple needle-punched non-woven fabric layers and laminating them through a barb machine, then heating to melt the L-PET inside the two PET staple needle-punched non-woven fabric layers to bond and fix various fibers to the latex layer, and finally rolling them; S4, preparation of flame retardant layer: prepare ingredients according to the flame retardant layer formula, add the prepared ingredients into a mixer for mixing, mix evenly, put into the mixer for low speed mixing, and finally put into the extruder for plasticization, pelletizing, die cutting and winding; S5. Preparation of waterproof, oil-proof and antistatic composite layer: the ingredients are prepared according to the formula of the waterproof, oil-proof and antistatic composite layer, the prepared materials are added to a mixer and mixed evenly, after being mixed evenly, transferred to a cooling mixer for low-speed mixing, and finally put into an extruder for plasticization, pelletizing, and finally die-cutting and winding; S6, composite processing: firstly, the prepared flame retardant layer is effectively composited with the back of the laminating layer through a hot stamping laminating machine, and then the prepared waterproof, oil-proof and antistatic composite layer is effectively composited with the flame retardant layer on the back of the laminating layer through a hot stamping laminating machine; S7, cutting and molding: The product is shaped, heated, and molded, anti-slip patterns are pressed on the surface, and air holes are punctured, and finally the product is cut and assembled into a car seat cover.
6. The method for preparing a car seat cover with good air permeability according to claim 5, characterized in that: The preparation method of the supramolecular solvent in S2 is as follows: dissolve a surfactant in tetrahydrofuran to obtain a 3-5 g / mL surfactant solvent, add 10-15 times the volume of water to the solution, vortex, and ultrasonicate for 10-15 min, then centrifuge to separate the phases, and take the lower layer, which is the supramolecular solvent.
7. The method for preparing a car seat cover with good air permeability according to claim 5, characterized in that: The concentration of acetic acid in the acetic acid-water mixture in S2 is 1-2% (v / v); the inorganic filling material is one or more of nano silicon dioxide, nano calcium carbonate, and nano aluminum carbonate; the silane modifier is one of tetraalkyltriethoxysilane, tetraalkyltrimethoxysilane, hexaalkyltriethoxysilane, and octaalkyltrimethoxysilane; the acetic acid-water mixture, natural latex, nano cellulose, inorganic filling material, glutaraldehyde, and silane modifier are 50-65 parts, 30-40 parts, 5-15 parts, 4-6 parts, 4-6 parts, and 3-5 parts by mass, respectively.
8. The method for preparing a car seat cover with good air permeability according to claim 7, characterized in that: The natural antibacterial agent in S2 is: coptis chinensis alcohol extract, garlic alcohol extract, and aloe alcohol extract are mixed in a mass ratio of 1:2-3:1; the oxidant is one or more of aloe water extract, grape seed alcohol extract, and tea alcohol extract; the pore-forming agent is one or more of water, ethanol, and ethyl acetate; the natural latex masterbatch, natural antibacterial agent, oxidant, nano-silica, and pore-forming agent are 75-85 parts, 4-6 parts, 1-4 parts, 5-15 parts, and 5-10 parts by mass, respectively.
Citation Information
Patent Citations
High strength and low elongation non-woven fabric for vehicle seats and manufacture method thereof
CN104149423A
Preparation method of natural antibacterial latex liner for underwear
CN110330702A
Abrasion-resistant seat cover for vehicle
CN215040848U
Wear-resistant sound insulation cloth for automobile seat
CN221392543U